1998
DOI: 10.1046/j.1365-2648.1998.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Is befriending by trained volunteers of value to people suffering from long‐term mental illness?

Abstract: People who suffer from long term mental illness may be vulnerable to loneliness and isolation when living in community settings. Befriending by volunteers may be an effective way of combating such problems and helping clients to develop social networks. The findings of a small scale project to evaluate the views of people suffering from long term mental illness of an organized befriending scheme are reported. Nine subjects who suffer from severe mental illness were interviewed, all subjects felt befriending wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 21 publications
1
53
1
1
Order By: Relevance
“…These researchers described programme recipients' experiences of the programme, but not the experience of volunteers. A similar study of volunteer befriending for SMI (Bradshaw & Haddock, 1998) found that participants reported the programme helped them, but the study described benefits in very general terms, did not discuss drawbacks, and did not explore either the perspectives of the befrienders or the mechanisms that promoted the benefits.…”
Section: Introductionmentioning
confidence: 99%
“…These researchers described programme recipients' experiences of the programme, but not the experience of volunteers. A similar study of volunteer befriending for SMI (Bradshaw & Haddock, 1998) found that participants reported the programme helped them, but the study described benefits in very general terms, did not discuss drawbacks, and did not explore either the perspectives of the befrienders or the mechanisms that promoted the benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Befriending in the form of providing companionship, social activities, and human contact was a primary role as well as promoting positive emotional well-being. The values of befriending schemes such as the reported Community Care Program are well recognised and potentially an effective way of combating loneliness and isolation and helping individuals to develop social networks [5].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that befriending others is a significant role of the neighbourhood volunteer [4,5] although other roles can include those of engaging with professionals in direct care partnerships [6], meeting nonmedical needs [7], manual work [8], and emotional support [9]. Befriending alone can be an effective way of relieving loneliness and isolation for those living in community settings, particularly if living alone, by helping them to communicate and develop social networks.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no clear evidence of the benefits of these interventions (Bradshaw & Haddock, 1998;Harris, Brown, & Robinson, 1999;Heslop, 2005;Mohr, 2004;Taggart, Short, & Barclay, 2000).…”
Section: Community-based Interventionmentioning
confidence: 99%